Meningkatkan Prestasi Belajar Bahasa Inggris Melalui Pembelajaran Kooperatif Model Team Game Tournament (TGT) Pada Siswa Kelas XI IPA 1 SMA Negeri 1 Malaka Barat Tahun Pelajaran 2022/2023 - Theresia Clara Nahak (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
The purpose of this study is to improve students' linguistic abilities in English through the Team Game Tournament (TGT) methodology. The driving force behind this inquiry stems from the less-than-ideal level of English proficiency detected among the eleventh graders of the science program at SMA Negeri 1 Malaka Barat throughout the 2022/2023 academic year. The study group consisted of 31 students enrolled in the grade eleven science program, part one. It is reasonable to assume that certain obstacles can be seen in efforts to increase linguistic talent, among them the utilization of linguistic competence for the purpose of social interaction and participation in recreational activities. The aim of this investigation is to evaluate the effectiveness of the fundamental approach used on the TGT platform with respect to students' linguistic proficiency in English. The aim of the inquiry was to evaluate the configuration of students enrolled in the Teams-Games-Tournament (TGT) curriculum. Utilization of multiple choice questions serves as a data collection method in the realm of the eleventh grade English course, especially with regard to Personal Correspondence subject matter. Initial and successive iteration of evaluations have the potential to provide in-depth discernment while scrutinizing student progress. The scientific findings from the student experiment showed a noteworthy increase from cycle I to cycle II, with a sizable jump from 58.06% to 93.55%. Empirical evidence suggests that involvement in TGT may have the capacity to enhance one's personal aptitude for understanding English. Eleventh graders of Science 1 SMA Negeri 1 West Malaka have succeeded in carrying out an innovative approach to English mastery pedagogy that is in line with the prescribed protocol.